Circadian Regulation of the Plant Transcriptome Under Natural Conditions - Panter, Paige E.; Muranaka, Tomoaki; Cuitun-Coronado, David; Graham, Calum A.; Yochikawa, Aline; Kudoh, Hiroshi; Dodd, Antony N. (Frontiers in Genetics, 2019)
Circadian rhythms produce a biological measure of the time of day. In plants, circadian regulation forms an essential adaptation to the fluctuating environment. Most of our knowledge of the molecular aspects of circadian regulation in plants is derived from laboratory experiments that are performed under controlled conditions. However, it is emerging that the circadian clock has complex roles in the coordination of the transcriptome under natural conditions, in both naturally occurring populations of plants and in crop species. In this review, we consider recent insights into circadian regulation under natural conditions. We examine how circadian regulation is integrated with the acute responses of plants to the daily and seasonally fluctuating environment that also presents environmental stresses, in order to coordinate the transcriptome and dynamically adapt plants to their continuously changing environment.